Membangun Fondasi Pancasila Sebagai Ideologi Nasional Bagi Umat Islam Indonesia - Dalmeri Dalmeri (Nizham Jurnal Studi Keislaman, 2018)
Pancasila as the foundation in the statehood for Muslims to the argument that was being carried by the political Islamic groups that received by the secular nationalist groups with prominent thinkers such as Sukarno. History shows the political Islamic groups still keen to make Islam as the basis of the state, with prominent thinkers such as Muhammad Natsir. The idea about the enforcement of shari'ah Islam in the state order in Indonesia back resounding through in the middle of the community after the state formed local regulations in some areas. This phenomenon can be understood as a reaction to the community dissatisfaction against the weak law enforcement in Indonesia. How to build Pancasila as the foundation and national ideology in the middle of the Islamic people in Indonesia who is very religious and diverse? This paper seeks to explore the position of Pancasila as the national ideology in the era of milinial is trying to describe the position of Pancasila as the ideology of nationhood and statehood that went from the historical approach through qualitative research method of primary sources that are very rampant cheating in view of Pancasila as the ideology of the Islamic people in Indonesia.